Water conservation and irrigation efficiency: a case study of Turlock Irrigation District's data management system for irrigation operations, environmental monitoring, and energy production - Walker, Noah, author; Malinky, Stan, author; Monier, Wes, author; Carkeet, Jason, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2012)
Current efforts in water conservation and irrigation efficiency illustrate the need for modern data management systems that that can consume, validate, calculate, manage and automate the reporting of real-time and historical water data with ease. Managing the vast amounts of data being collected along with the ability to dynamically link to water resource management models, are key requirements for irrigation districts. The problem presented in this paper is the availability of Commercial Off-The-Shelf (COTS) solutions that provide a stable decision support platform for water conservation and irrigation efficiency efforts while offering additional capabilities in the areas of environmental monitoring and energy production. The Turlock Irrigation's approach to solving this problem is based on WISKI: a comprehensive COTS solution that manages and automates the entire process of data collection, import, validation, editing, reporting, and exporting with advanced editing capabilities. The KISTERS WISKI (Water Information System KISTERS) solution can integrate with all in-house data collection systems, including water resource management models and offers users a wide range of tools for water data management. Automation of the routine data management tasks performed by District staff reduces the lag time between data collection and decision-making, thus increasing their overall operational efficiency. Streamlining the entire process from data collection to reporting in one solution has also improved the District's ability to conserve water and focus on revenue generating opportunities like energy production. WISKI makes information available in near real-time to District staff, thereby reducing the amount of time and money spent generating good data for decision-making. The use of cumbersome and error-prone spreadsheets, as well as custom in-house developed data management solutions have been phased out as COTS solutions like those from KISTERS offer a viable alternative without the hassle. Without a solution like WISKI, that accommodates all the District's interests, in addition to saving its engineers and hydrologists valuable time and money, the District would not be as efficient as it is today.
Irrigated agriculture responds to water use challenges
Presented at Irrigated agriculture responds to water use challenges - strategies for success: USCID water management conference held on April 3-6, 2012 in Austin, Texas.